Perbandingan Glukosa Metode Carik Celup Vitamin C 500 Mg pada Penderita Diabetes Melitus Tipe 2 - Adriansyah; Didi Irwadi; Nurul Anggrieni (Politeknik Baubau, 2023)
Vitamin C is a water-soluble vitamin and is naturally present in food. Humans cannot synthesize vitamin C, so it must be obtained from outside and food as the main source. However, taking vitamin C before a urine glucose test can cause a false positive result for some people. The purpose of this study was to analyze the comparison of the results of urine glucose levels using the strip dip method before and after consuming 500 mg vitamin C in people with type 2 diabetes mellitus. This type of research is pre-experimental with a One-group pre-post test design that assesses the causal relationship with the intervention, namely the consumption of Vitamin C in urine samples that have previously been examined for urine glucose. The population in this study were type 2 diabetes mellitus patients who were treated at the Harapan Baru Health Center and the sampling technique used purposive sampling with a total sample of 33 samples. This research was conducted at the Clinical Chemistry Laboratory of the East Kalimantan Ministry of Health Polytechnic. The results of the examination of 33 respondents showed that the percentage of results had increased by 84.5%. The normality test using the Shapiro-Wilk statistical test showed that it was significant before and after consuming vitamin C of 0.000. This shows that these values are not normally distributed. The Wilcoxon statistical test showed a significant value of 0.000 with a significance level of 0.05, i.e. 0.000 <0.05, so it can be concluded that there was an increase in glucose results for urine chemistry examination by dipping method after consuming 500 mg of vitamin C in patients with type 2 diabetes mellitus.